(untitled) (AMJ (Advanced Medical Journal), 2023)
Background and objectives: Some clinical studies have suggested that cigarette smoking may be associated with hearing loss. The objective of this study is to evaluate the association between smoking and hearing loss and to characterize the type of hearing loss found in smokers. Methods: A hospital-based cross-sectional study conducted on 100 cases aged between 20-50 years, 70 cases were smokers and 30 were non-smokers. All the participants were examined by an Otoscope, a Tuning Fork, Tympanometry and Pure Tune air conduction and bone conduction Audiogram. Audiogram results were analyzed and hearing loss was defined as hearing threshold greater than 25 dB HL at one or more of frequencies (0.25,0.5, 1, 2,4 and 8 kHz). The type, severity and involved frequencies of hearing loss were analyzed based on the pure tone average. Results: The number of cases with hearing loss was 26 cases, 22 of them were smokers and 4 were non-smokers. Smoking significantly increased the risk of hearing loss (p value = 0.04). Smokers were 2.3 times more likely to have hearing impairment as non-smoker. High frequency sensorineural hearing loss was the predominant type among smokers and the severity ranged from mild to severe, mild loss was the most common. The severity of hearing loss was affected significantly by the intensity and the duration of smoking. Conclusions: Cigarette smoking affects the hearing ability after exclusions of most possible factors including noise exposure. It increases the risk of hearing impairment with increasing age in a dose related manner.